DESIGN AND CONSTRUCTION OF A NATURAL DISASTER DETECTION EQUIPMENT USING THE WATER LEVEL SWITCH SENSOR AND SENSOR SW-420 - mardiana; Meidi Wani Lestari; Third (Politeknik Negeri Medan, 2021)
Disasters such as earthquakes, tsunamis, floods and others always cause losses in the form of material, psychological can also cause casualties. To avoid the occurrence of greater losses, an early disaster warning and information system is needed to provide opportunities for self-rescue so that losses can be minimized. The basic concept of the Internet of Things (IoT)